Oral Bioavailability and Plasma Disposition of Pefloxacin in Healthy Broiler Chickens - Martínez, María-Aránzazu; Ares, Irma; Rodríguez, José-Luis; Martínez, Marta; Martínez-Larrañaga, María-Rosa; Isea, Gerardo; Anadón, Arturo (Frontiers in Veterinary Science, 2017)
Pefloxacin was given to two groups of eight healthy broiler chickens at a dose of 10 mg/kg BW, intravenously (IV) or orally. For 24 h, plasma concentration was monitored serially after each administration. Concentrations of pefloxacin and its major metabolite N-demethyl pefloxacin (norfloxacin) were measured by use of high-performance liquid chromatography. After IV and oral administration, plasma drug concentration-time curves were best described by a two-compartment open model. For pefloxacin, the elimination half-life (t½ beta) was 8.44 ± 0.48 h and 13.18 ± 0.82 h after IV and oral administration, respectively. After single oral administration, pefloxacin was rapidly absorbed with an absorption half-life (t½a) and TMAX of 0.87 ± 0.07 and 2.01 ± 0.12 h, respectively. Maximum plasma concentration (CMAX) was 4.02 ± 0.31 μg/mL . Oral bioavailability of pefloxacin was found to be 70 ± 2 %. A fraction of pefloxacin was metabolized to N-demethyl pefloxacin (norfloxacin). This metabolite represented 5% of the parent drug. The maximal plasma concentration (CMAX) of N-demethyl pefloxacin (norfloxacin) was calculated as 0.19 ± 0.01 mg/mL. The t½ beta of N-demethyl pefloxacin after oral pefloxacin administration was 10.93 ± 0.80 h. Analysis of pharmacokinetic data obtained in this study reveals that an oral dose of 10 mg pefloxacin/kg BW, every 24 h, should be appropriate for control of the most infections in chickens.